Hubungan motivasi belajar terharap prestasi belajar pada mahasiswa semester III - Septia Ratna Dewi; Rohayati Masitoh; Rosiana Nur Imallah (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Academic achievement of nursing students is an important indicator of educational success as it reflects the academic and professional readiness of prospective nurses in facing the demands of clinical practice and the workforce. Theoretically, one internal factor believed to influence academic achievement is learning motivation, as motivation encourages students to actively engage in the learning process, sustain learning efforts, and achieve expected academic goals, particularly among nursing students who face complex academic and practical workloads. Purpose:  To determine the relationship between learning motivation and academic achievement among third-semester undergraduate nursing students. Results: Data analysis using the Spearman Rank correlation test showed a correlation coefficient of -0.025 with a significance value of p = 0.778, indicating no significant relationship between learning motivation and academic achievement among third-semester nursing students at Universitas ‘Aisyiyah Yogyakarta. The negative and very weak correlation suggests that differences in learning motivation levels were not followed by meaningful differences in Grade Point Average (GPA). Therefore, the null hypothesis (Ho) was accepted and the alternative hypothesis (Ha) was rejected. Conclusion: There is no significant relationship between learning motivation and academic achievement among third-semester undergraduate nursing students.